A General History of the Science and Practice of Music - Hawkins, John 1719-1789 (London Payne, 1776)
Sir John Hawkins (1719-1789) was an English magistrate, writer, and author of the first history of music in English. Hawkins was apprenticed as a clerk and became a solicitor. In 1759 a legacy enabled him to sell his practice. A Middlesex magistrate from 1761, Hawkins was elected chairman of the quarter sessions in 1765. He was knighted in 1772. Hawkins's General History of the Science and Practice of Music occupied him for sixteen years. It was published in five volumes in 1776, a few weeks before Charles Burney's celebrated General History of Music. Hawkins's book continues to be invaluable as a mine of detailed information, some of it unavailable elsewhere, but it was eclipsed by Burney's.
A late 19th-century edition of this work is also available in the library
Ex libris A. von Ahn Carse (plate)
Leather-bound, with marbled endpapers, marbled edges, embossed in gold
Keywords: Past; 18th Century (1701-1800); Music history; Europe; a =; Abbatini, A.M.; actrice; ad lib bezetting; ad lib. bezetting; Adami da Bologna, A.A.; Adami da Bolsena, A; Adami, A; Addison; Agricola; akoestiek; Albinoni; Albinoni, T; alchemie; alchemie; alcohol; alcohol; Aldrich; Aldrich, H; Aldrich, H; Allegri; Allegri, G; allemande; Anerio, F; Anerio, F; Arcadelt; Arcadelt; Ariosti, A; artikulatie; artikulatie; Artusi; Artusi; Astorga, d'; Avison, C; Avison, C; Bach, C.P.E.; Bach, J.B.; Bach, J.Chr.; Bach, J.Chr. Fr; Bach, J.Christian; Bach, J.M.; Bevin, E; bezetting (voc.); bezetting (vocaal); Biber; bibliotheek; bibliotheek; bibliotheek; Ban, A; Blainville; Barre, De la; blokfluit; blokfluit; blokfluit; Blow, J; Blow, J